Zakat Collection Strategy to Enhance Financial System Capabilities National Zakat in Support of the Ummah's Economy - Utami, Pertiwi; Ali, Juhary; Suryanto, Tulus (Journal of Islamic Economic and Business Research, 2025)
This research investigated how zakat collection strategies can be carried out through the role of government, GCG, the decision to pay zakat and the trust of the community. The aim is to increase opportunities for the national zakat financial system carried out by the Central National Zakat Amil Agency (BAZNAS) to support the ummah's economy. A case study research design with a quantitative approach guided the research. Outer model analysis with the help of Smart PLS was used to identify scores for research variable indicators. The four findings are as follows: the role of government through technological indicators needs to be improved for better zakat management, GCG through effectiveness and efficiency indicators in processes and institutions needs to produce output that can meet community needs while making the best use of resources, high public trust through a dynamic relationship between Amil Zakat, OPZ, and the public must be created as well as possible, and the decision to pay zakat through increasing technological competence plays an important role in supporting zakat collection strategies, especially those based on digitalization. Thus, it can be concluded that based on Muzzaki's perception of zakat collection strategies, the four main indicators with the highest scores for each variable can increase the opportunity for the national zakat financial system to contribute to supporting the ummah's economy. The government in collaboration with BAZNAS needs to pay serious attention to strategic efforts to increase public trust in BAZNAS, especially through word-of-mouth promotion strategies, outreach, education, implementation of information technology, and also reducing high operational costs by emphasizing efficiency and good management.